The Effect of Providing Tomato Juice on the Hemoglobin Concentration of Pregnant Women - Hatima, Husnul; Hafsah, Hafsah; Sulistyowati, Endang (Journal of Pharmaceutical and Health Research, 2024)
Pregnant women are a vulnerable group prone to malnutrition-induced anemia. In 2023, Puskesmas Tamamaung reported a staggering 73.9% prevalence of anemia among pregnant women. Anemia in pregnancy poses risks such as maternal mortality, miscarriage, intrauterine growth retardation, and postpartum hemorrhage. To address this, tomato juice, rich in vitamin C crucial for iron absorption, is proposed as a potential solution to enhance hemoglobin levels.The objective of this quasi-experimental study is to assess the efficacy of tomato juice supplementation in increasing hemoglobin (Hb) levels among pregnant women diagnosed with anemia. A quasi-experimental study utilizing a pre-test post-test non-equivalent control group design was conducted. The study population comprised 28 second and third-trimester pregnant women with anemia registered at Puskesmas Tamamaung from February to March 2024. All 28 participants were included as the total sample. Data were collected using observation sheets and hemoglobin measurement tools. Paired t-tests and independent t-tests were employed for data analysis.Significant differences were observed in hemoglobin levels before and after tomato juice consumption among pregnant women at Puskesmas Tamamaung. Tomato juice supplementation was found to be more effective in increasing hemoglobin levels compared to iron tablet supplementation alone.Tomato juice facilitates hemoglobin synthesis by expediting the process from erythroblasts to normoblasts and reticulocytes, thereby accelerating hemoglobin formation.The administration of tomato juice effectively increases hemoglobin levels among pregnant women with anemia. This underscores the potential of tomato juice as a supplementary intervention in combating maternal anemia during pregnancy.